The syntax of wh-questions in unaccusative and (Un)ergative structures in Mehri language: A Phase-based approach - Fakih, Abdul-Hafeed; Al-Qumairi, Saeed Saad; Alzubi, Ali Abbas Falah (PloS one, 2023)
The Mehri Language is an endangered language spoken in eastern Yemen, a sub-group of the Semitic language family, and a Southern Arabic language. The syntax of Mehri wh-questions has not been explored within minimalism; hence, there is a morpho-syntactic need to provide a modern analysis of wh-questions in order to show how the interrogative structures can be derived. This study aims to examine the syntax of the wh-question movement in Mehri’s unaccusative/ergative and unergative structures and answer the following questions within Chomsky’s (2000 and 2008) Phase-based Theory: (i) Does the Mehri language allow fronting of wh-phrases to [Spec-CP]? And (ii) how can wh-movement in Mehri unaccusative and (un)ergative structures be accounted for? This work presents a novel analysis of wh-question movement in unaccusative/ergative and unergative structures in Mehri; it demonstrates that the source head C triggers the movement of wh-adjunct and wh-subject phrases. In wh-adjunct extraction, two strategies are employed: overt wh-fronting and wh-in-situ; when the head Foc inherits an edge feature from C, wh-adjunct overtly undergoes movement from its original position within v*P to the left peripheries of [Spec-FocP] and subsequently to [Spec-CP]. When the lexical wh-adjunct remains within v*P, its question features covertly move to [Spec-CP], because the head Foc does not inherit an edge feature from C. In wh-subject extraction, the wh-subject overly undergoes movement to [Spec-CP] because C obligatorily inherits the edge feature to the head Top, which triggers movement of the illogical subject in unaccusative/ergative structures and the logical external specifier in unergative structures to [Spec-CP]. Moreover, Mehri obeys the Phase Impenetrability Condition of Chomsky, where wh-subject and wh-adjunct phrases must pass through certain phases until [Spec-CP].